2022
DOI: 10.1021/acssuschemeng.1c07157
|View full text |Cite
|
Sign up to set email alerts
|

Ordered Mesoporous Carbon Encapsulating KF: Efficient and Stable Solid Base for Biodiesel and Fine Chemical Catalytic Synthesis

Abstract: Developing efficient and reusable catalysts to transform raw feedstocks into high value-added fine chemicals and biofuels has received considerable research interest. Herein, we report ordered mesoporous carbon (OMC) encapsulating KF to design novel chainmail solid base catalysts (KF@OMC-x, where x stands for the weight ratio of potassium). The OMC armor can be facilely prepared from a one-step mechanochemical synthesis without the assistance of any solvents, which was achieved from the grinding of resorcinol,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…No Cu−Cu coordination of the Cu foil was found (Figure 1e), further revealing the isolated dispersion of Cu single atoms without aggregation into particles [21] . N 2 adsorption‐desorption isotherms (Figures S14–S15) showed that the BET surface area of the Cu‐MOF was lower than that of d‐MOF (788 vs. 1063 m 2 g −1 ), but their pore size distributions were similar, indicating that Cu ions combine with UiO‐66‐NH 2 defects (d‐MOF) and may partially occupy the pores of MOF [23] …”
Section: Methodsmentioning
confidence: 99%
“…No Cu−Cu coordination of the Cu foil was found (Figure 1e), further revealing the isolated dispersion of Cu single atoms without aggregation into particles [21] . N 2 adsorption‐desorption isotherms (Figures S14–S15) showed that the BET surface area of the Cu‐MOF was lower than that of d‐MOF (788 vs. 1063 m 2 g −1 ), but their pore size distributions were similar, indicating that Cu ions combine with UiO‐66‐NH 2 defects (d‐MOF) and may partially occupy the pores of MOF [23] …”
Section: Methodsmentioning
confidence: 99%
“…Encapsulation is a novel strategy for heterogeneous ILs, where active species are physically accommodated in highly porous materials ( Zheng et al, 2022 ). Compared with the immobilization method in which the active sites of the catalyst are fixed on the support, the active sites of the catalyst synthesized by the encapsulation strategy are flowable and free, which can promote the activity of the catalyst ( Kong et al, 2016 ).…”
Section: Ionic Liquid-functionalized Metal–organic Frameworkmentioning
confidence: 99%
“…A variety of solid catalysts have been used in biomass conversion to desired fuels and commodity chemicals over the past 3-4 decades. As a consequence, several articles have been published highlighting the production of bio-based fuels and valuable chemicals, which are mostly focused on different conversion pathways. However, the catalytic behavior of recyclable heterogeneous porous nanomaterials still needs to be explored for the upgradation in the biomass conversion processes. The past decades have witnessed utilization of solid acid catalysts, as they exhibited stimulating catalytic activity and selectivity with superior reusability. , In this regard, the nanoporous catalysts have an advantage due to their large accessible surface-active sites, pore tunability, and easily adjustable surface wettability, which effectively controls the product selectivity, adsorption, and diffusion of incoming bio-based oxygenated feedstocks.…”
Section: Introductionmentioning
confidence: 99%